Implementasi Model Cooperative Learning Tipe STAD dalam Meningkatkan Hasil Belajar IPA di SDN 08 Lubuk Dalam - Firmansyah; Hayuani; Hadijah, Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ science learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model at SDN 08 Lubuk Dalam. This research employed the Classroom Action Research (CAR) method, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The research subjects were fifth-grade students who faced difficulties in understanding science concepts. Data were collected through learning outcome tests, student and teacher activity observations, and interviews. The findings indicated that the implementation of the STAD model significantly improved students’ learning outcomes. In the first cycle, there was an increase in students’ active participation in group discussions, although learning outcomes were not yet optimal. In the second cycle, students’ learning outcomes improved significantly, with an average score reaching the "very good" category. Moreover, the STAD model also enhanced students’ social skills, such as cooperation, responsibility, and communication. Challenges in implementing this model included time constraints and students’ adaptation to the new learning method. However, with appropriate strategies, such as effective time management and intensive teacher guidance, these obstacles could be overcome. In conclusion, the STAD cooperative learning model has proven effective in enhancing students’ science learning outcomes and can serve as an innovative instructional strategy in elementary schools.